Managing Digital Innovation Units—Life Cycle, Transitions, and Growth Traps: Companies can use digital innovation units (DIUs) to spur innovation, but DIU leaders must actively manage two dynamic loops—Smooth Operator and Shape Shifter—and navigate three critical growth traps for DIUs to be successful. Issue 5 (3rd September 2022) - Trischler, Matthias; Bason, Christian; Li-Ying, Jason
Overview: Digital transformation presents a major challenge for many incumbents. Digital laggards are falling further behind frontrunners and digital-born startups. To make up some ground, more firms resort to experimentation with and implementation of digital innovation units (DIU). While knowledge about types of DIUs and their challenges is helpful, little is known about how to manage DIUs along the DIU's development life cycle and the parent organization's digital transformation process. Based on an exploratory study of six DIUs, we identify two dynamic and embedded loops that DIU leaders need to actively manage: DIU leaders ensure a smooth transition between the lifecycle stages in the first loop, while avoiding critical growth traps in the second loop. We provide practical guidance for how to manage DIUs for sustainable impact.